2011
DOI: 10.1007/s10549-011-1561-8
|View full text |Cite
|
Sign up to set email alerts
|

Detection of isolated ipsilateral regional lymph node recurrences by F18-fluorodeoxyglucose positron emission tomography–CT in follow-up of postoperative breast cancer patients

Abstract: Imaging diagnostic methods except for mammograms are not recommended for follow-up of postoperative breast cancer patients in order to detect small recurrences because of the poor survival improvement in earlier randomized trials. However, the use of new imaging modalities may improve survival by detection of small isolated regional lymph node recurrences which are potentially curable. Between April 2006 and December 2008, we used PET-CT to find small recurrences in follow-up of 1,907 postoperative breast canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Both Lanitis et al [9] and Chang et al [10] analyzed axillary metastatic disease or synchronous ipsilateral supraclavicular lymph node metastases as primary diagnosis rather than recurrence after the primary diagnosis of breast cancer. Ohsumi et al [11] described the detection of ipsilateral regional lymph node recurrence using positron emission tomography-computed tomography. Moossdorff et al [12] reviewed the literature to determine the prognosis after contralateral lymph node recurrence in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Both Lanitis et al [9] and Chang et al [10] analyzed axillary metastatic disease or synchronous ipsilateral supraclavicular lymph node metastases as primary diagnosis rather than recurrence after the primary diagnosis of breast cancer. Ohsumi et al [11] described the detection of ipsilateral regional lymph node recurrence using positron emission tomography-computed tomography. Moossdorff et al [12] reviewed the literature to determine the prognosis after contralateral lymph node recurrence in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Ohsumi S et al [12] reported the incidence of isolated extra-axillary node recurrences to be 1.2%. However, the incidence demonstrated in the present study was approximately 3%, which is 2.5 times higher than that reported in the aforementioned study.…”
Section: Discussionmentioning
confidence: 99%
“…F-18 fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT), on the other hand, is a useful diagnostic modality that can detect small lymph node recurrences including extra-axillary node metastases [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Based on FDG-PET/CTpositive loco-regional LN metastases (defined as the ALNs, supraclavicular LNs, and IMLNs), the rates of LNs in the IMC region were 3.7% for patients with primary M0 cancer and 9.5% for patients with primary M1 cancer, while the rates increased to 9.4% for patients with recurrent M0 cancer and 11.8% for recurrent M1 cancer [42]. Regardless of the imaging modality, follow-up results have indicated that the overall rate of clinically detectable IMLN recurrences remains < 1.5% after primary systemic breast cancer treatment, even when the regional IMLNs were not irradiated [12,[67][68][69][70][71] (Table 2). In addition, the IMLN recurrence rate was reduced to 0.2% for patient who had undergone IMLN radiotherapy (IMLN RT) [12].…”
Section: Imln Recurrence After Treatmentmentioning
confidence: 99%